2015
DOI: 10.1016/j.sbspro.2015.01.714
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Sexual and Emotional Development: The Role of Romantic Relationships

Abstract: The physiological processes occurring during adolescence, often so abrupt, threaten the permanence of the previously constructed sense of identity, questioning the patterns and representations that had governed the relations of the teenager with his body and with his relational systems. Although puberty is not only reduced to sexual transformations, definitions centered mainly on this aspect can be found in the literature. In fact, pubertal development is the acquisition disclosure index of adult reproductive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 16 publications
2
9
0
1
Order By: Relevance
“…The findings suggested that a concurrent involvement in a committed romantic relationship for more than three months functioned as an ARA resource. This is in line with previous literature supporting the significance of engagement in romantic relationships for adolescents [1,30,32]. Furthermore, it is reinforced by research indicating the positive behavioural impact on general adaptation that results from the engagement of adolescents in romantic relationships [31].…”
Section: Involvement In a Romantic Relationship In Understanding Presupporting
confidence: 91%
See 1 more Smart Citation
“…The findings suggested that a concurrent involvement in a committed romantic relationship for more than three months functioned as an ARA resource. This is in line with previous literature supporting the significance of engagement in romantic relationships for adolescents [1,30,32]. Furthermore, it is reinforced by research indicating the positive behavioural impact on general adaptation that results from the engagement of adolescents in romantic relationships [31].…”
Section: Involvement In a Romantic Relationship In Understanding Presupporting
confidence: 91%
“…On top of age-, and gender-related influences on romantic attachment, there is strong evidence supporting the importance of involvement in romantic relationships during adolescence [1,30]. Some studies indicate that involvement in a romantic relationship during adolescence may act as a protective factor for adolescents' general adaptation precipitating higher levels of psychological wellbeing [31,32]. In contrast, other studies demonstrate that the engagement in romantic relationships in adolescence may be associated with higher delinquent behaviours, signs of depression, and suicidal behaviour [33,34].…”
Section: Romantic Involvement Influences In Romantic Attachment In Admentioning
confidence: 99%
“…First romantic relationships offer youth the opportunities to develop positive communication skills (Salerno, Tosto, & Antony, ). Our results suggest that the first romantic experiences of dyads with balanced interactions constituted a positive experience, and an opportunity to grow as an individual, since they showed the ability to reveal themselves respectfully while being attentive to their partner’s thoughts and feelings by late adolescence.…”
Section: Discussionmentioning
confidence: 99%
“…Youth tend to fully explore romantic relationships around middle adolescence (i.e., 15–17 years) and to consolidate romantic bonds during late adolescence (i.e., 18–20 years; Connolly & McIsaac, ). These new experiences offer opportunities to build skills, such as self‐disclosure, reciprocity, and empathy, which will help establish and maintain future romantic relationships (Salerno, Tosto, & Antony, ). Before late adolescence, adolescents’ perception of their own romantic relationships seems to be more positive than the perception of outside observers, as adolescents tend to see these relationships as special and unique (Florsheim & Moore, ).…”
Section: Conflicts and Conflict Resolution Strategies In Romantic Relmentioning
confidence: 99%
“…On top of age-, and gender-related influences on romantic attachment, there is strong evidence supporting the importance of involvement in romantic relationships during adolescence [ 1 , 30 ]. Some studies indicate that involvement in a romantic relationship during adolescence may act as a protective factor for adolescents’ general adaptation precipitating higher levels of psychological wellbeing [ 31 , 32 ]. In contrast, other studies demonstrate that the engagement in romantic relationships in adolescence may be associated with higher delinquent behaviours, signs of depression, and suicidal behaviour [ 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%